Determinan Sikap dan Minat Keperilakuan Individu Menggunakan Internet Stock Trading - Steven Morris Lawrence; Zaki Baridwan (Jurnal Ilmiah Mahasiswa FEB, 2013)
The objective of this research is to examine factors that influence attitude and intention to use internet stock trading services with modified models of Technology Acceptance Model (TAM) developed by Davis  (1989), Theory of Planned Behavior (TPB) developed by Ajzen (1991), Decomposed Theory of Planned Behavior (DTPB) developed by Taylor and Todd (1995), as a development of the model used by Lee (2009) and Chau et al. (2001). This research used survey method to collect data. Samples of this research were investors in Malang City, Indonesia who had ever used internet stock trading services. A total of 141 data can be analyzed by using Smart PLS (Partial Least Square) software. The result of this research shows that perceived usefulness, trust, and compatibility have positive significant effect to attitude and then the attitude has positive significant effect to intention. Whereas perceived risk, perceived benefit and perceive ease of use did not influence the attitude. It means that the behavioral intention to use internet stock  trading is influenced by the attitude toward using internet stock trading, and the attitude is influenced by perceived usefulness, trust and compatibility. The implication of this research is relevant for the management of the securities company and information system analyst to be more consider factors of attitude, perceived usefulness, trust and compatibility in applying and developing internet stock trading in their system.     Keywords:   Technology Acceptance Model  (TAM),  Theory of Planned Behavior  (TPB), Decomposed Theory of Planned Behavior  (DTPB), internet stock trading, behavioral intention, attitude, perceived usefulness, trust, compatibility.